(untitled) (Annals of Medical Research, 2022)
Aim: We designed this study with the intention of determining the prevalence of sarcopenia and the association between sarcopenia findings and the severity of COVID-19 disease in COVID-19 patients. Materials and Methods: As the study group, 92 patients aged 50 and over years old and whose PCR test results were positive and 45 days passed after the test result and recovered, 92 healthy individuals over 50 years of age, who were not infected with COVID-19 , were included in the study group. Results: While 33.7% of the patient group had severe sarcopenia, 7.61% sarcopenia, 30.43% probable sarcopenia, 28.26% did not have sarcopenia. While 3.26% severe sarcopenia and 10.87% probable sarcopenia were observed in the control group, 85.87% sarcopenia was not observed. The incidence of sarcopenia in the patient group was significantly higher than in the control group (p<0.001).When all participants were divided into 2 groups as 50-65 years old and over 65 years old, sarcopenia was observed at a rate of 32.65% in the 50-65 age group patient group, while sarcopenia was observed at a rate of 1.39% in the control group. While sarcopenia was observed, 10% of the control group had sarcopenia. Conclusion: The findings of this study show that people with the COVID-19 infection had an increased frequency of sarcopenia.